The impact of AI service failure on human employee behavior and customer service performance - Tian, Jian; Lin, Hongxia; Tourky, Marwa; Cheng, Bao (Emerald, 2025)
Purpose: This study aims to investigate how and when artificial intelligence (AI) service failure stimulates employees’ differentiated work behaviors. Design/methodology/approach: A multi-wave, multi-source survey involving 284 employee-supervisor pairs was conducted across 15 four-star and five-star hotels in Guangzhou, China. Hierarchical multiple regression analysis was used to test the hypotheses. Findings: Findings suggest that AI service failure induces schadenfreude toward the organization among employees with low perceived insider status, which then leads to procrastination behavior; however, it triggers sympathy toward the organization among employees with high perceived insider status, which further results in proactive customer service performance (PCSP). Practical implications: Their work offers practical insights for tourism and hospitality companies on promoting PCSP and reducing procrastination behaviors among service employees in response to AI service failures. Originality/value: By incorporating perceived insider status as a moderator, and examining the mediating roles of schadenfreude and sympathy toward the organization, this research enhances the theoretical understanding of AI service failure and its consequences from the employee perspective.
Keywords: 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; Sport, Leisure & Tourism; 3504 Commercial services; 3506 Marketing; 3508 Tourism; AI service failure; Perceived insider status; Procrastination behavior; Proactive customer service performance